The Effect of Active Learning Methods Terjun-Tulis-Saji to the Improvement of Scientific Literacy and Mastery of Biology Competencies of Senior High School Students - Wirastini Komang Ayu; Herawati Susilo; Hadi Suwono (International Conference on Education and Language (ICEL), 2014)
The Science Curriculum 2013 is designed to develop students’ scientific literacy. Scientific literacy involves mastery of science concept, process skill, attitude, as well as writing skill. This study investigated the attainment of scientific literacy and biology competencies of 10th grade science students at SMAK Kolese Santo Yusup, Malang, Indonesia. The method of this study was quasi experiment by using nonequivalent pretest posttest control group design. Based on existing theoretical framework, assessment were developed to know the concept mastery, ability to apply biology concept to solve authentic problem, and publish the findings through on line social media. To improve student’s scientific literacy, the active learning model called Terjun Tulis Saji (TTS) was applied. The TTS method guided the students to collect data and information based on their question or problem, analyze of the data and information to construct new understanding and thinking, represent and communicate the findings. The result of the study showed significant differences of scientific literacy and biology competencies between control and experiment group. The effect of TTS on scientific literacy and biology competencies of students in biology lesson were discussed.